Marketing Research of the Medical Institution in the System of Voluntary Medical Insurance for Making Managerial Decisions - A. B. Tsvetkova; R. Kh. Yunisov (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The segment of voluntary medical insurance is a promising type of insurance. This situation encourages insurers to develop advanced competitive products with continuously upgrading level of service. It is very important to pay special attention to legal and medical and economic protection of the ensured. It is clear that the insurance company needs data of marketing research for its efficient work. However, we should bear in mind that one party of the voluntary medical insurance is a medical institution, which is involved in the process and understands the importance of marketing information system data while signing the contract with the insurance company. Systematized data of the medical institution gives an opportunity to choose an optimal partner. The article using the example of NMHC named after N.I.Pirogov shows which data is analyzed by the medical institution and why and demonstrates how the mechanism of making decision about choosing the insurance company looks like. It was highlighted that using the internal information could allow the medical institution to save money and time necessary to process data and make the final decision. The authors ground recommendations for using the research in the process of signing the contract with the insurance company, a relevant model was built as an illustration.